PENGEMBANGAN KOMIK BERBASIS PROBLEM BASED LEARNING MATERI BANGUN DATAR UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Putri Ema Amalia, Atika; Nugraheni, Nursiwi (Jurnal Muara Pendidikan, 2024)
Mathematical communication skills are very important for students. Therefore, this research aims to improve these abilities through the development of PBL-based mathematical comics on plane material. This research is Research and Development (R&D) type with the Borg and Gall model. The research was conducted at SDN 1 Soborejo and SDN 3 Tuksongo in the same cluster, and the subjects were class IV students. This comic learning media development project was validated by three experts in the fields of media, materials and language. Data collection techniques used questionnaires, interviews, evaluation questions and documentation. This media is considered suitable to be applied as a learning medium because it has passed validation tests by experts with a score of 81% in the adequate category. In comparison, teacher responses reached 93%, and student responses reached 90% with very good qualifications. This PBL-based mathematics comic media has influence based on the results of the pretest and posttest in the large class test, which was tested using a Paired sample T-test. The results of the effectiveness test show a posttest significance value of 0.000 < 0.05, so Ho is rejected, and Ha is accepted and shows that there is a significant influence in using this media to improve students' mathematical communication skills.